Engineering the Architecture of Elastin‐Like Polypeptides: From Unimers to Hierarchical Self‐Assembly. Issue 3 (3rd February 2020) - Saha, Soumen; Banskota, Samagya; Roberts, Stefan; Kirmani, Nadia; Chilkoti, Ashutosh
Abstract: Well‐defined tunable nanostructures formed through the hierarchical self‐assembly of peptide building blocks have drawn significant attention due to their potential applications in biomedical science. Artificial protein polymers derived from elastin‐like polypeptides (ELPs), which are based on the repeating sequence of tropoelastin (the water‐soluble precursor to elastin), provide a promising platform for creating nanostructures due to their biocompatibility, ease of synthesis, and customizable architecture. By designing the sequence and composition of ELPs at the gene level, their physicochemical properties can be controlled to a degree that is unmatched by synthetic polymers. A variety of ELP‐based nanostructures are designed, inspired by the self‐assembly of elastin and other proteins in biological systems. The choice of building blocks determines not only the physical properties of the nanostructures, but also their self‐assembly into architectures ranging from spherical micelles to elongated nanofibers. This review focuses on the molecular determinants of ELP and ELP‐hybrid self‐assembly and formation of spherical, rod‐like, worm‐like, fibrillar, and vesicle architectures. A brief discussion of the potential biomedical applications of these supramolecular assemblies is also included. Abstract : Protein polymers derived from elastin‐like polypeptides (ELPs) provide a modular platform to create hierarchical structures with varying (nano, meso, and micro) size with remarkable biosafety and tunability. This review highlights the molecular determinants that control the molecular architecture and hierarchical self‐assemblies of ELP and ELP‐hybrid materials. The biomedical applications of such self‐assemblies are also discussed briefly.